Ganjar Pranowo's Personal Branding Analysis on Instagram - Tawakkal, Mohammad Azzam; Rochmaniah, Ainur (Universitas Muhammadiyah Sidoarjo, 2024)
Political actors use social media to increase public trust in them and build their image in the eyes of society. Politicians will shape people's perception of themselves and political communication will be easier with their personal branding on social media. One of the most active political actors is Ganjar Pranowo, who uses social media, especially Instagram, to communicate with his people. This article aims to explain the suitability of Ganjar Pranowo in forming personal branding which he carried out through uploads on Instagram social media based on eight basic concepts of personal branding. This research study was conducted using a descriptive qualitative approach. The results show that Ganjar Pranowo uses eight basic concepts of personal branding as a strategy for creating successful personal branding, which makes him closer to society and grows people's trust in him. Apart from that, his efforts to build personal branding through social media have an impact on Ganjar Pranowo's image in the eyes of the public. This was proven by the election of Ganjar Pranowo as governor of Central Java for two terms and his success in becoming one of the candidates for the 2024 presidential election of the Republic of Indonesia.